The speedy tortoise - Hackett, Joe; Spoor, Mike (Wayland London, 2011)
Animal School is a series of four books at Purple Band 8 of the Start Reading programme. The stories centre around the animals at Animal School. Each character is the opposite of what you would expect- a cowardly lion, a speedy tortoise, a pig who doesn't like getting dirty and a frog who is afraid of the water.